Certificate-Based Signature Scheme for Industrial Internet of Things Using Hyperelliptic Curve Cryptography. (8th February 2022) - Ullah, Insaf; Alkhalifah, Ali; Althobaiti, Maha M.; Al-Wesabi, Fahd N.; Hilal, Anwer Mustafa; Khan, Muhammad Asghar; Ming-Tai Wu, Jimmy
Abstract : The Industrial Internet of Things (IIoT) is a technology that uses the Internet of Things (IoT) infrastructure to sense, process, and communicate real-time events in the industrial system to cut down on unnecessary operating costs and to speed up industrial automation of internal and external working processes. Since the IIoT system inherits the same cyber-physical vulnerabilities that the IoT system already encounters, it requires additional work to address security concerns owing to its heterogeneous nature. As a result, an efficient security mechanism is essential to protect against various and unknown cyber-attacks. In this article, we propose a certificate-based signature scheme based on hyperelliptic curve cryptography (HECC), with the aim of improving security while reducing computational and communication costs in the IIoT environment. The proposed scheme outperforms existing schemes in terms of both computational and communication costs, as well as offering better security.